On the Margins of Art and Society: Traces of “The Promise of Happiness” in the Art Practices of Neriman Polat - Yıldız Öztürk (Sanat Tarihi Yıllığı)
Neriman Polat was born in 1968 in İstanbul and majored in art in the Fine Arts Faculty of Mimar Sinan Fine Arts University. Beginning in the second half of the 1990s, she participated in contemporary art exhibitions in Turkey and abroad and in art collectives such as The Definition of Art Group, In Between, and Excavation in addition to her personal productions. Her works deal with diverse themes such as collective memory, modernization, male violence, activities of daily living, family, home, urban environments, immigration, social class, ethnicity, gender, and sexual orientation. This study analyzes Neriman Polat’s artistic practices and expressions with the aid of a critical approach to Sara Ahmed’s definition of happiness. Specifically, this article focuses on three of Polat’s exhibitions: Merciless (2018), Flower Wound (2019), and Breaking the Seal (2019). The main study data sources are exhibition catalogs, press releases, articles from exhibition critics, artist-curator conversations, and personal observations collected from exhibitions. In all three exhibitions, the audience is faced with different aspects of home, family, women, and children that society has ignored, hidden, or made invisible. Ahmed, in her book The Promise of Happiness, excavates the concept of happiness, examining different sociological and cultural processes to explore what happiness hides and what it costs. Both Neriman Polat and Sara Ahmed discuss power mechanisms with relational approaches, investigate the possibilities of a pluralistic society, and create alternative archives.